Synthesis of alternating D–A1–D–A2 terpolymers comprising two electron-deficient moieties, quinoxaline and benzothiadiazole units for photovoltaic applications. Issue 24 (18th May 2016) - Keshtov, M. L.; Khokhlov, A. R.; Kuklin, S. A.; Chen, F. C.; Nikolaev, A. Y.; Koukaras, E. N.; Sharma, G. D.
Abstract : Two new regular (D–A1–D–A2) terpolymersP1 andP2 containing two electron-deficient moieties, quinoxaline and benzothiadiazole, were designed and synthesized. Abstract : Two new regular (D–A1–D–A2) terpolymersP1 andP2 containing two electron-deficient moieties, quinoxaline and benzothiadiazole, were designed and synthesized. The resulting copolymers exhibit high thermal stability, broad absorption in the range of 300 to 950 nm, low E g of both 1.36 and 1.57 eV, as well as deep HOMO energy levels of −5.24 and −5.62 eV. Such properties are useful in improving photovoltaic properties. Polymer solar cells (PSCs) based on optimizedP1 :PC71 BM andP2 :PC71 BM (1 : 2 by weight) active layers with a 3 v% DIO/CF additive displayed a power conversion efficiency (PCE) of 5.28% ( V oc of 0.93 V, J sc of 10.28 mA cm −2 and FF of 0.55) and 5.54% ( V oc of 0.80 V, J sc of 12.18 mA cm −2 and FF of 0.57), respectively, under illumination of AM1.5G (100 mW cm −2 ). In order to increase the PCE further, the DIO/CF processed active layer was subjected to methanol treatment that resulted in a PCE increase up to 7.13% and 7.59% for theP1 :PC71 BM andP2 :PC71 BM based devices, respectively. The methanol treatment increases all of the photovoltaic parameters, which is attributed to the lowering of series resistance, an increase of hole mobility, and reduction of charge recombination due to enlarged built-in potential.